Pemanfaatan Media Pembelajaran Interaktif Lectora Inspire Untuk Motivasi Belajar Siswa - Bagus Rizki Lubis; Novika Wulandari; Tursina Juliani Dlt; Ali Ikhwan (CV. ITTC INDONESIA, 2022)
Information and communication technology (ICT) innovation is progressing rapidly. The use of ICT in education is becoming more popular. Various advances and supporting applications have been created in the field of education. As a lesson planner, teachers should use a variety of appropriate learning tools and resources to plan lessons and help students learn quickly and effectively. The Lectora Inspire application is used to discuss learning resources using interactive teaching technology. Lectora Inspire is designed for beginners and its features make it easy to create learning materials and test or assessment materials. Through teacher training in primary education, the development of engaging and intuitive learning media is taking place. The Lectora Inspire application allows teachers to easily create unique interactive learning environments that can adapt to the student's situation, environment and needs. The strategy used is to build learning development institutions that use computer learning environments as learning tools. The aim is to create interactive learning media containing study instructions and exam questions. SDN 068332 Jalan Rami 4 No.6, Mangga, Medan Tuntungan District, Medan City, Medan City, North Sumatra, War der Ort for Dieses Training.